Chickpea production restored through upscaling crowdsourcing winner varieties and planting date adjustments in the Ada’a district, East Shoa zone, Ethiopia - Mengistu, Dejene Kassahun; Terefe, Hailu; Teshome, Tadesse; Garamu, Talila; Lakew, Basazen Fantahun; Fadda, Carlo (Elsevier, 2024)
Chickpea is an important cash crop for Ada’a farmers as it does for farmers in Ethiopia and elsewhere in the world. Its production, however, has been dwindling due to biotic and abiotic stresses. According to participant farmers from Ada’a district, the production of chickpea in some Kebeles of Ada’a such as Gubasaye has been abandoned because of root rot and foliar diseases such as fusarium wilt. This paper presents the evaluation of upscaled varieties’ performance assessed by metric data as well as through beneficiary farmers’ self-assessment data. Recognizant to the problem, five varieties of chickpea tested in the Goro district of the Southwest Shoa zone, were introduced as part of the upscaling of crowdsourcing winner crop varieties in Ethiopia. Crowdsourcing is an approach of outsourcing variety evaluation, selection, and dissemination to volunteer crowds of farmers. The introduction of the winner varieties and adjustment of the planting time was found effective in the Ada’a district. Higher grain yield was obtained from the upscaled winner varieties in the range of 2.4–2.53 t/ha, with slight variations over varieties. Habru variety showed slightly higher performance than the others. Survey participant farmers have reported an increase in GY due to growing the winner varieties compared with varieties they used to grow before and gained higher annual income due to higher productivity, market demand of the upscaled varieties, and premium market price with 6–25 Ethiopian birr (ETB) per kilogram of sold grain of these varieties. High productivity is attributed to the genetic potential of the varieties, their response to farm management, and better adaptation to the local growing conditions. Participant farmers perceived that their livelihood has been improving because of the adoption of the upscaled varieties’ productivity and market demand. The annual income of participant farmers is estimated to be 2500 to 181,000 ETB for growing the winner varieties. The results indicate that upscaling pre-tested chickpea varieties and delaying their planting time to early September are effective mechanisms for reducing yield loss to fusarium wilt and root rot diseases. It can be inferred that using the crowdsourcing approach for variety evaluation and selection for upscaling is a robust approach to improve the adoption and dissemination of improved agricultural technologies.